Behavior of reinforced concrete tapered beams. (March 2022) - Al-Ahmed, Ali Hussein Ali; Al-Zuhairi, Alaa Hussein; Hasan, Ammar Mousa
Abstract: Long span framed buildings and simply supported bridges produce high bending moment and deflection at mid-span. For these structures, using conventional prismatic beams with high depth shall be uneconomic. In such instances; using tapered beams may be considered a viable alternative to overcome this issue. There is lack of experimental and analytical studies on the behavior of reinforced concrete tapered beams (RCTBs) having mid-span depth enlargement. This research introduces experimental and finite elements method (FEM) study on the behavior of RCTBs with mid-span depth enlargement and different tapering angles and reinforcement configurations. Accordingly, six RCTBs and one prismatic beam were cast and tested up to failure. The test RCTBs were divided into two groups (three tapered beams for each group) depending on the tapering angle. Consequently, tapering angles of about 20° and 36° were adopted for beams of Group I and Group II, respectively. For each group, three different reinforcement configurations were adopted. It is observed from test results that RCTBs reinforced with bottom bent rebars have developed higher ultimate strength, stiffness and toughness compared with those beams having other reinforcement configurations. However, for RCTB with tapering angle of about 20° and reinforced with bottom bent rebars, a somewhat small reduction in ultimate strength of about 16% with gain in weight of about 27% was recorded compared to the prismatic beam. FEM using ABAQUS software was used to simulate the test beams. Good agreement was obtained between the experimental and FEM results in terms of load-deflection response and crack pattern. Moreover, the FEM study was extended to cover a reasonable range of tapering angles (17° to 45°) and bottom bent reinforcement ratios (0.0031 to 0.0086). It is observed from numerical results that decreasing of the tapering angle from 45° to 17° resulted in a significant increase in the ultimate load, initial stiffness and toughness and decreasing the mid-span deflection within entire range of loading. In addition, normalized charts were presented in this study to easily estimate the ultimate strength, initial stiffness, and toughness of a RCTB having a certain tapering angle and bottom bent reinforcement ratio.